Mucoepidermoid Carcinoma in a Minor Salivary Gland in a Child - Fatih Sengul; Sera Simsek; Binali Cakur (Case Reports in Dentistry)
Mucoepidermoid carcinoma (MEC), one of the most common salivary gland malignancies, is rare in children. MEC mainly occurs in the parotid gland, along with minor glands being the second common site, particularly in palate. Clinical, histological, and radiological findings of palatal MEC in a 12-year-old girl are presented with three-year follow-up. Pathologic lesions must be considered in differential diagnoses of intraoral asymptomatic lesions, and their detailed inspection should be taken into consideration.